Epilepsy and Fine Motor Function - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Kocaeli University, Pediatric Neurology OP Clinic, Turkey, studied the relationship between fine motor skills and seizure and treatment parameters in 44 children with rolandic epilepsy (RE) and compared to 44 healthy controls.